Debate and considerations on using videos for cultural heritage from social media for 3D modelling - Themistocleous, Kyriacos (My University, 2016)
Social media can be used as a new source of information by archaeologists and cultural heritage experts to access cultural heritage-related videos for creating 3D models using Structure for Motion techniques. There is a vast amount of data now available on social media, which are posted every day on the internet. However, there is confusion regarding if such data is considered fair use, public domain, creative commons or copyrighted. Indeed, social medias, such as Facebook, Twitter, Instagram and YouTube, have different regulations regarding ownership and republishing videos. This paper will discuss how social media can be used for cultural heritage research, especially if video data is used, transformed or repurposed for 3D modelling.
Keywords: Copyright; Creative commons; Cultural heritage; Documentation; Fair use; Public domain; Social media; Video